FOODLIT-PRO: conceptual and empirical development of the food literacy wheel - Rosas, Raquel Alexandra Ferreira (2021)
Pursuing food systems' sustainability is crucial. Given the risk constituted by unhealthy diets, scarce research on food-related adjacent fields, and inconsistency across food literacy conceptualizations, this study aims to explore the constructs' definition and develop a conceptual and empirical framework of food literacy. A quantitative approach was taken on previously obtained qualitative outcomes from 30 interviews with experts from food-related fields. Food literacy was defined by a four-dimension model: Cooking Skills, Preserve and Analyse, Choice and Acquisition, Search and Plan. The framework Food Literacy Wheel integrates the construct definition, food literacy determinants (Internal, External) and influential factors (Nutritional, Psychological, Health, Learning Contexts, Policy, Industry, Sustainability, Social and Cultural). Allowing a broader perspective of food literacy within major food systems, this study contributes with new insights for future instruments and interventions, paving the way to develop/implement food literacy-related multi-sectorial and multilevel actions.